Comparative Evaluation of IL-1β levels in Gingival Crevicular Fluid (GCF) of the Teeth Supporting Porcelain Fused to Metal Crowns (P.F.M) - Sirous Risbaf Fakour (Journal of Global Pharma Technology, 2017)
Background and Objective: Using fused to metal porcelain as crowns is the most common methods of replacing missing teeth.IL-1-beta plays a key role in immunity and inflammation. Gingival crevicular fluid (GCF) reflecting the periodontal inflammation was sampled in the same area. This study aimed to compare the amount of IL-1β in the GCF of porcelain -fused to metal crowns with that of healthy teeth. Method: This case-control study was performed on 16 people with porcelain- fused to metal crowns with clinically acceptable standards. The history of non-systemic disease, not smoking and taking any regular medications up to 6 past months was taken. Healthy teeth corresponding to veneered teeth in the opposite side of the jaw were selected as control group. After the initial sampling the teeth received a phase of a non-surgical dental treatment, and the sampling was repeated at 1 and 3 months after the initial sampling. After collecting data with SPSS23 statistical software the data was entered into computer.To compare the concentrations of IL-1β in the two groups Paired t-test was used. Results: The concentration of IL-1β at the all three intervals of testing in teeth with porcelain fused to metal crowns was higher than of it in the control group (P< 0.001). Furthermore, the concentration of IL-1β was decreased in both groups during the whole time. (P<0.001 & P<0.003). Conclusion: The concentration of IL-1β in GCF of teeth with porcelain- fused to metal crowns with clinically acceptable standards is higher than of that in healthy teeth. Porcelain- fused to metal crowns are involved in the production of IL-1β.Keywords: IL-1β, porcelain- fused to metal crowns, GCF, PFM.